2021
DOI: 10.1038/s41598-021-97975-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fertilizer practice on fungal and actinobacterial cellulolytic community with different humified particle-size fractions in double-cropping field

Abstract: Cellulose plays an important role in maintaining or improving soil carbon (C) cycling and soil fertility of paddy field. There had close relationship between functional cellulose genes (cbhI and GH48) with characterize of soil organic matter chemical components (fulvic acid and humic acid) and soil physical fractions. However, there is still limited information about how functional cellulose degradation response to long-term fertilizer management and their relative importance for C sequestration under the doub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…According to our results, greater development of cellulolytic microorganisms was found in both variants with an organic-mineral fertilization system (O1MFS and O2MFS). Other data [77] from a 34-yearlong regime of fertilization experiments also showed a significant increase in the number of cellulolytic microbial communities with the use of crop remains, organic manure, and chemical fertilizers compared with unfertilized soils. Based on this fact, we conclude that in conditions of long-term use of various fertilization systems, the development of cellulolytic organisms increases in the case of a combination of mineral and organic fertilizers, which have a significant content of undecomposed plant remains (straw, siderate).…”
Section: Cellulolytic Microorganismsmentioning
confidence: 85%
“…According to our results, greater development of cellulolytic microorganisms was found in both variants with an organic-mineral fertilization system (O1MFS and O2MFS). Other data [77] from a 34-yearlong regime of fertilization experiments also showed a significant increase in the number of cellulolytic microbial communities with the use of crop remains, organic manure, and chemical fertilizers compared with unfertilized soils. Based on this fact, we conclude that in conditions of long-term use of various fertilization systems, the development of cellulolytic organisms increases in the case of a combination of mineral and organic fertilizers, which have a significant content of undecomposed plant remains (straw, siderate).…”
Section: Cellulolytic Microorganismsmentioning
confidence: 85%
“…Figures 1 – 3 depict the dynamics of cellulose substrate decomposition in different types of arable soils under various fertilisation systems. Various types of fertilisers had distinct and notable impacts on the activation of cellulolytic microorganisms, which play a key role in breaking down plant-based biopolymers ( Tang et al, 2021 ). Notably, these microorganisms thrived in scenarios where organic fertilisers, such as manure and cover crops, were applied.…”
Section: Resultsmentioning
confidence: 99%
“…Tian et al found that inoculation of cellulolytic fungal increased the abundance of Aspergillus (genus level), thus significantly accelerating the cellulose degradation process. Similarly, Tang et al showed that organic manure combined with rice straw and chemical fertilizers significantly increased cbh I community abundance. Therefore, the cellulolytic fungal glycoside hydrolase family 7 cellobiohydrolase I gene ( cbh I) often acted as a suitable biomarker to explore SOC degradation. ,, Zhang et al found that long-term application of mineral fertilizers together with pig manure significantly increased the abundance of the cbh I cellulolytic fungal gene.…”
Section: Introductionmentioning
confidence: 93%